PENGEMBANGAN PROGRAM PERKULIAHAN BIOLOGI KONSERVASI DENGAN PENDEKATAN KONTEKSTUAL BERBASIS KEARIFAN LOKAL ACEH UNTUK MENINGKATKAN LITERASI LINGKUNGAN DAN TINDAKAN KONSERVASI - Apriani, Evi (2012)
This study was conducted to develop a tutorial program for conservation biology through Acehnese local wisdom-based contextual approach to improve their environmental literacy and conservation measures. Preliminary studywas conducted in the Department of Biology Education involving 27 students and two biology lecturers.This preliminary study revealed that lecturers did not link the material with students' real-life situations in accordancewith the context of life of the Acehnese people. They also did not discuss the conservation measures which were currently practiced by the Acehnese peoplein the form of local wisdom and Acehnesecustom. In fact, the local wisdom of Aceh is still existed andpracticed by its people.Therefore, it must be maintained through Conservation Biology course.Based on the initial data,Conservation Biology course through Acehnese local wisdom-based contextual approach was developed.Course programs and Acehnese local wisdom-based context was tested on a limited scale involving 30 students, three learning observers in the classroom, and seven learning observers outside the classroom.The implementation of the program involved 33 students, four learning observers in the classroom, and seven learning observers outside the classroom.Data collection was conducted through need analysis, documentation, observation, interviews, questionnaires, and tests.Analysis of qualitative data include transcription, tabulation, coding, and descriptions in accordancewith the research focus.Quantitative data was then processed using the N-gain on the results of the pretest and posttest.This study has resulted in two products, namely 29 pairs of Acehnese local wisdom-based context and conservation biology course throughAcehnese local wisdom-based contextual approach canbe implemented with varying methods.The study also found that conservation biology course program with Acehnese local wisdom-based contextual approach can improve the environmental literacy of students (N-gain = 46%) and increase conservation measures of students by maintaining(74%), preserving(62%), and fixing(56%).